2012
DOI: 10.1590/s1806-37132012000400006
|View full text |Cite
|
Sign up to set email alerts
|

Achados de fibrobroncoscopia em pacientes com diagnóstico de neoplasia pulmonar

Abstract: Objective: To compile fiberoptic bronchoscopy findings in patients diagnosed with lung cancer and to correlate those with histopathological findings. Methods: This was a retrospective study involving 212 patients with a confirmed diagnosis of lung cancer by cytological evaluation of BAL specimens or by histopathological evaluation of endobronchial or transbronchial biopsy specimens. The data were collected at the Respiratory Endoscopy Section of Hospital São Salvador, located in the city of Goiânia, Brazil, be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Postoperative specimens are used to determine pleural and lymph node invasions, but cannot help identify endobronchial metastasis. Since early lung adenocarcinoma can expand along the bronchus [4], bronchoscopy can accurately assess endobronchial metastasis; however, the traditional endoscopic examination aims mainly to obtain pathological diagnosis and does not guide in selecting a surgical procedure for peripheral lung adenocarcinoma in the aspect of endobronchial metastasis [5]. In this study, endobronchial metastasis was defined as grades 2 or 3 invasions in central bronchial anatomic regions in patients with lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative specimens are used to determine pleural and lymph node invasions, but cannot help identify endobronchial metastasis. Since early lung adenocarcinoma can expand along the bronchus [4], bronchoscopy can accurately assess endobronchial metastasis; however, the traditional endoscopic examination aims mainly to obtain pathological diagnosis and does not guide in selecting a surgical procedure for peripheral lung adenocarcinoma in the aspect of endobronchial metastasis [5]. In this study, endobronchial metastasis was defined as grades 2 or 3 invasions in central bronchial anatomic regions in patients with lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings correlate with Buccheri G. study [23].The findings of the present study in sample of Iraqi patients, are in agreement with those reported in these studies and underscore the importance of a standardized description of fiber optic bronchoscopy findings as a tool in the diagnosis of lung cancer. [23,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…A título de comparação, esse procedimento correspondeu a cerca de 70% dos cânceres diagnosticados nos Estados Unidos, segundo o National Cancer Database 18 . Contudo, já está em discussão, como melhoria do painel, a inclusão, em um primeiro momento, do procedimento citopatológico, considerado importante no diagnóstico do câncer de pulmão 19 .…”
Section: -10unclassified